Financing of municipal current expenditure through local taxes: a systematic review - Henry Bernardo Garay Canales; Julio Mayorga Challco; Wilson Eduardo Vargas Cubas; Fredy Roger Flores Flores (Qubahan Academic Journal)
This study examines key factors influencing the financing of municipal current expenditure through local taxes, emphasizing the importance of strengthening local tax resources to enhance municipal fiscal autonomy. A systematic literature review was conducted using Scopus and Web of Science databases, focusing on keywords such as financing, municipal current expenditure, and local taxes. The review included 19 articles in Spanish and English published between 2014-2022. Findings indicate that local tax autonomy, diversified tax structures, economic cycles, tax culture, effective enforcement, and local political commitment significantly affect municipalities' self-financing capacity. Property taxes and intergovernmental tax coordination also play crucial roles. The interplay of strategic, institutional, and contextual elements determines local governments' ability to finance expenditures and investments through self-administered taxes. Evidence suggests that municipalities effectively harmonizing these variables may reduce their dependence on discretionary central transfers, gaining autonomy in defining budgetary priorities according to local needs. The study provides a foundation for comprehensive municipal tax reforms aimed at increasing local fiscal independence. Finally, the study's findings offer practical guidance for implementing comprehensive municipal tax reforms, potentially leading to enhanced fiscal autonomy and more sustainable local government financing.